ANALYSIS OF FISHING PORTS TO SUPPORT THE DEVELOPMENT OF TUNA FISHERIES IN THE SOUTH COAST OF JAVA - Tri Wiji Nurani; Ernani Lubis; John Haluan; Sudirman Saad (Research Center for Fisheries, 2010)
Construction of a fishing port requires special conditions to be properly developed. The right choice of location from the land and water aspects is the basic requirement to build a fishing port facilities.